DEVELOPMENT OF EXPERT JUDGMENT-BASED ISLAMIC EDUCATION LEARNING MATERIALS ON WORSHIP PRACTICES TO ENHANCE STUDENTS’ UNDERSTANDING AND PARTICIPATION - Fitriyanti Fitriyanti; Eprianto Eprianto; Indah Wigati; Suhadi Suhadi (Jurnal Konseling Pendidikan Islam, 2026)
This study aimed to develop and validate an interactive learning media for Islamic Religious Education (PAI) on the topic of worship practices for senior high school students at SMAN 1 Rantau Bayur. The research employed the Research and Development (R&D) method using the ADDIE instructional design model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. Data were collected through interviews, classroom observations, documentation, and expert validation questionnaires. The developed product was evaluated by one material expert and one media expert using a five-point Likert scale. The findings indicated that conventional teaching methods, dominated by lectures and simple demonstrations, limited students’ engagement and understanding of worship practices. The interactive learning media was designed by integrating multimedia elements, including instructional videos, animations, illustrations, narration, and interactive quizzes, to facilitate meaningful and student-centered learning. Expert validation demonstrated that the product achieved a feasibility score of 94% from the material expert and 93% from the media expert, with an overall average of 93.5%, categorized as "very feasible." These results confirm that the developed learning media meets pedagogical, technical, and instructional quality standards. The study concludes that interactive multimedia developed through a systematic instructional design process can enhance the quality of Islamic Religious Education by increasing students’ understanding, learning motivation, and active participation. The developed media is recommended as an innovative instructional resource for improving worship practice learning in senior high schools.